Kuormittavuustekijät, koettu stressi, työtyytyväisyys ja sosiaaliset tukiverkostot ammattilaisjääkiekkoilijan arjessa - Konttinen, N.; Mononen, K.; Jaakola, T. (Research Institute for Olympic Sports, 2020)
The purpose of this project was to investigate the extent to which the issues related to both stress and well-being at work show up in the everyday life of professional ice hockey players playing in the Finnish major league called Liiga. The aim was to gather information about players` experiences that could be used to support players` health, coping with stress, and well-being in their daily lives. The research ques-tions were related to four key themes: stress factors in a player`s daily life, perceived general stress, work satisfaction, and social support network.The data were collected between the end of February and the beginning of March in 2020, just before the hockey season 2019-20 was cancelled prematurely due to the coronavirus pandemic. A paper questionnaire was applied as the research method. At the time of the survey, the total number of hockey players playing in the Liiga was estimated to be 419 players. A total of 223 players responded to the survey, giving an overall estimated response rate of 53.2.